CAUSALITY BETWEEN ECONOMIC GROWTH AND UNEMPLOYMENTIN INDONESIA - Muh. Hamzah; Fitriyah (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to examine the causal relationship between economic growth and the unemployment rate in Indonesia for the 2019–2023 period. This study uses of a quantitative approach with the data from the Statistics Indonesia and Bank Indonesia. Data is analyzed using Vector errors Correction model (VECM), Impulse response function (IRF), and Variance Decomposition version estimation. The research outcomes display that there is no short run causal relationship among economic growth and unemployment. However, the cointegration test shows that there may be a long-run relationship between the two variables. The VECM estimates show that each variable adjusts to long-run imbalances. The IRF and variance decomposition analyses confirm that the influence of one variable on another is relatively weak in the short run. However, the result shows the dynamics of adjustment in the long run. These findings highlight the importance of a long run economic policy approach that not only focuses on growth but also considers structural factors in the labor market to effectively address unemployment.